QUANTITATIVE ADJECTIVES IN KULISUSU LANGUAGE - Nurfarsil, Eca; Tambunan, Tambunan; Rohmana, Rohmana (Journal of Teaching of English, 2020)
This research aimed at investigating  the quantitative adjectives and semantic types of quantitative  adjectives in  Kulisusu language. The scope of this research was quantitative adjectives and semantic types of quantitative adjective meaning color, size, form and taste. The research questions of this study were "what is the form quantitative adjectives in Kulisusu language" and "what is the semantic type of quantitative adjectives in Kulisusu language. This research used qualitative descriptive by applying some techniques of collecting data such as :  (1) translation, (2) introspection (3) elicitation and interview.  Instrument of Indonesian word of adjective. After  the data being collected, the data were analyzed by using   the following steps : (1) identify the form of adjectives, (2) determine the form of adjectives,  and (3) determine the meaning of adjectives.The  result of the research  showed that Kulisusu language had  six kinds of quantitative adjective gathered  in this research namely  ompole, sade’ete, samentonga, malingumo and  o’opa.  And there are seven kinds of semantic types of quantitative adjectives meaning color  namely , mea, kuni, bula, yijo, kangura, and wungu. Furthermore  adjective meaning in term could be seen  of lines that make it consist of shapes that have straight lines, shapes that have curved lines, and shapes that have mixed lines, namely straight lines and curved lines. After that adjective meaning the size in detail  twelve types of subordinates namely (1.) distance size, (2,)  long size, (3.)  high, size (4.)   broad size, (5.)  depth size, (6)  thickness size, (7.)  content size (8.) amount size, (9.) time size, (10.) heavy size, (11) big size, and (12.) age size. The last adjective meaning of  taste includes  (1.) a state  that symbolizes the ambiences of the mind (2.) a taste that symbolizes of  the mood, and (3.) a taste that symbolizes the senses.